PENGARUH KOMITE AUDIT, KEPEMILIKAN MANAJERIAL DAN KUALITAS AUDIT TERHADAP PENCEGAHAN FRAUD (Studi Kasus Pada Perusahaan BUMN yang Terdaftar di Bursa Efek Indonesia) PERIODE 2022-2024 - Estiaglory Rense, Clara Glenny; Dewi Astuti, Tutut (ITB AAS Indonesia Surakarta, 2025)
This study was conducted to determine and analyze the influence of the audit committee, managerial ownership, and audit quality on fraud prevention (a case study of state-owned enterprises listed on the Indonesia Stock Exchange for the 2022-2024 period). The population of this study was all state-owned enterprises that committed fraud or fraudulent financial statements listed on the Indonesia Stock Exchange for the 2022-2024 period. The data analysis tool used was SPSS. The results of the study indicate that the Audit Committee has a positive effect on Fraud Prevention in state-owned enterprises listed on the Indonesia Stock Exchange during the 2022-2024 period. Managerial Ownership has a positive effect on Fraud Prevention in state-owned enterprises listed on the Indonesia Stock Exchange during the 2022-2024 period. Audit Quality has a positive effect on Fraud Prevention in state-owned enterprises listed on the Indonesia Stock Exchange during the 2022-2024 period. Furthermore, it is hoped that the results obtained can be more comprehensive and have a broader contribution to the development of science.